(untitled) (Global Journals of Research in Engineering, 2012)
In any information system intrusions are the activities that damage the security and integrity of the system. In this paper we focus on wireless network, intrusions in wireless network (WLAN) and different Distributed Intrusion Detection Systems which are used to detect these attacks or intrusions. The rapid enhancement in wireless network has changed the level of network security. So, past of protecting the network with the firewalls are not sufficient to maintain network security in wireless local area network. There are different intrusion detection techniques which are used for identifying the various types of intrusions in wireless local area network. In this paper, we compare the various Distributed intrusion detection Systems used for detecting attacks in wireless network and also make a comparison table of these DIDS depending upon the performance. This comparison table will very helpful in designing better intrusion detection systems for detecting and preventing of vulnerabilities in wireless network.